Prevalence and genetic characterization of Cryptosporidium in pre-weaned cattle in Urmia (Northwestern Iran) - Mahmoud Mahmoudi; Khosrow Hazrati Tapeh; Esmaeil Abasi; Hojjat Sayyadi; Arash Aminpour (Journal of Infection in Developing Countries)
Introduction: Cryptosporidiosis is a zoonotic disease causing digestive problems in pre-weaned calves. Considering the zoonosis of the parasite and its importance in veterinary medicine, we evaluated the prevalence and genotyping of Cryptosporidium spp. in diarrheic pre-weaned calves in the northwest of Iran.